Pengaruh Profitabilitas, Solvabilitas dan Pertumbuhan Perusahaan terhadap Manajemen Laba - Deni Kurniyanto; Gendro Wiyono; Risal Rinofah (Universitas Batanghari Jambi, 2023)
This research aims to determine the effect of profitability, solvency and company growth on earnings management in food and beverage companies listed on the Indonesia Stock Exchange for the 2017-2021 period. The population used in this study are food and beverage companies listed on the IDX for the 2017-2021 period. Profitability, solvency, company growth are independent variables, while earnings management is the dependent variable. The results of the partial test (t test) show that profitability has an effect on earnings management due to a significant value of 0.03 <0.05 and a calculated t value of 2.117 > 1.994. While the solvency and growth of the company have no effect on earnings management.